Neurofunctional mapping of reward anticipation and outcome for major depressive disorder: a voxel-based meta-analysis - Yang, Xun; Su, Yueyue; Yang, Fan; Song, Yuan; Yan, Jiangnan; Luo, Ya; Zeng, Jianguang (Psychological medicine, 2022)
Aberrations in how people form expectations about rewards and how they respond to receiving rewards are thought to underlie major depressive disorder (MDD). However, the underlying mechanism linking the appetitive reward system, specifically anticipation and outcome, is still not fully understood. To examine the neural correlates of monetary anticipation and outcome in currently depressed subjects with MDD, we performed two separate voxel-wise meta-analyses of functional neuroimaging studies using the monetary incentive delay task. During reward anticipation, the depressed patients exhibited an increased response in the bilateral middle cingulate cortex (MCC) extending to the anterior cingulate cortex, the medial prefrontal cortex, the left inferior frontal gyrus (IFG), and the postcentral gyrus, but a reduced response in the mesolimbic circuit, including the left striatum, insula, amygdala, right cerebellum, striatum, and IFG, compared to controls. During the outcome stage, MDD showed higher activity in the left inferior temporal gyrus, and lower activity in the mesocortical pathway, including the bilateral MCC, left caudate nucleus, precentral gyrus, thalamus, cerebellum, right striatum, insula, IFG, middle frontal gyrus, and temporal pole. Our findings suggest that cMDD may be characterised by state-dependent hyper-responsivity in cortical regions during the anticipation phase, and hypo-responsivity of the mesocortico-limbic circuit across the two phases of the reward response. Our study showed dissociable neural circuit responses to monetary stimuli during reward anticipation and outcome, which help to understand the dysfunction in different aspects of reward processing, particularly motivational v. hedonic deficits in depression.